(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: One common procedure is laparoscopic transabdominal preperitoneal (TAPP) inguinal hernia repair. Fixation versus non-fixation mesh placement is still debatable, nevertheless, especially when it comes to the results of postoperative pain. Objective: To compare the impact of mesh fixation versus non-fixation on acute and chronic groin pain following laparoscopic TAPP inguinal hernia repair. Materials and Method: A prospective comparative study was conducted at Jinnah Postgraduate Medical Center Karachi, from January 2024 to June 2024. Patients were divided into two groups based on mesh fixation method. Postoperative pain was assessed using the Visual Analogue Scale (VAS) at 8, 16, and 24 hours, day 7, and at 3 months follow-up, in-person or telephonically. Results: Patients in the non-fixation group showed significantly lower VAS scores at all intervals. Chronic groin pain at 3 months was notably reduced in this group, with no hernia recurrence in either cohort. Conclusion: Non-fixation of mesh offers superior outcomes in terms of pain reduction without compromising surgical success.